Extremophilic Microfactories: Applications in Metal and Radionuclide Bioremediation - Marques, Catarina R. (Frontiers in Microbiology, 2018)
Metals and radionuclides (M&Rs) are a worldwide concern claiming for resilient, efficient and sustainable clean-up measures aligned with environmental protection goals and global change constraints. The unique defense mechanisms of extremophilic bacteria and archaea have been proving usefulness towards M&Rs bioremediation. Hence, extremophiles can be viewed as microfactories capable of providing specific and controlled services (i.e., genetic/metabolic mechanisms) and/or products (e.g., biomolecules) for that purpose. However, the natural physiological plasticity of such extremophilic microfactories can be further explored to nourish different hallmarks of M&R bioremediation, which are scantly approached in the literature and were never integrated. Therefore, this review not only briefly describes major valuable extremophilic pathways for M&R bioremediation, as it highlights the advances, challenges and gaps from the interplay of ‘omics’ and biological engineering to improve extremophilic microfactories performance for M&R clean-up. Microfactories’ potentialities are also envisaged to close the M&R bioremediation processes and shift the classical idea of never ‘getting rid’ of M&Rs into making them ‘the belle of the ball’ through bio-recycling and bio-recovering techniques.